Perfil de crianças com síndrome congênita por vírus Zika em um hospital de referência de Mato Grosso, de 2015 a 2017 - Lima, Solange da Silva (2018)
Introduction: The Zika (ZIKV) outbreak infection had its first occurrence in Brazil at the end of 2015, in the northeastern region, spreading quickly through the states of the country, being associated with the decrease of the head circumference growth at birth and a number of neurological and structural complications. Objective: The main purpose of this study is to verify the profile of children with congenital Zika virus syndrome, who were treated at a reference hospital in Mato Grosso between the years of 2015 to 2017 according to severity, their families sociodemographic characteristics, maternal infection occurrence and the main associated comorbidities. Method: It was conducted a quantitative and descriptive study of which the manipulated pediatric data was registered in the Patient’s Health Record, Record of Patients and Registration of Events in Public Health form (RESP-MICROCEPHALY) from the reference hospital. In case of missing information, the mothers of newborns were contacted by phone calls in order to fill out their data. Results: Among 46 children with the syndrome, three (3) were born in 2015, forty (40) in 2016 and three (3) in 2017, all of them from 23 different cities of Mato Grosso, with a higher occurrence in Cuiabá, Várzea Grande and Tangará da Serra. The profile of their mothers was characterized by predominantly aged in childbirth between 20 and 30 years (73,92%), self-reported race/color as brown (67,39%), 60,87% with complete high school, 52,17% being single, 65,21% reported being a housewife, 66,87% had a family income to 1 minimum wage. According to the live-born classification and the severity of microcephaly, 6 preterm children, 9 at term children had microcephaly at birth followed by three preterm, 25 at term and 2 post-term with severe microcephaly. One of the cases progressed to microcephaly after a year. The most recurring alterations on the diagnostic imaging were the calcifications (45,16%), ventriculomegaly (24,24%), hydrocephalus (18,75%). Such changes have been detected between 22 to 39 weeks of gestation, especially on 38 and 39 weeks. The symptoms of infection are more common in the first trimester and are characterized by fever, exanthema, pruritus, joint pain, muscle soreness and conjunctival hyperemia. Tests for Syphilis, Toxoplasmosis, Rubella, Cytomegalovirus, Herpes and Zika virus (STORCH) were performed on mothers and children, founding two cases of Herpes 1 and 2 infection, one of them was a preterm child whose serology test came back as negative at birth, but was positive at corrected age of 7 months and 11 days; only one of the mothers had positive serology. The most frequent alterations were on at term children with severe microcephaly who presented subcortical calcifications, visual alterations, arthrogryposis, hydrocephalus and ventriculomegaly. Conclusion: The health record findings of the children treated at the Infectious and Parasitic Diseases Outpatient Clinic of the reference hospital in Mato Grosso corroborate results from other studies, reinforcing the causality relationship between microcephaly and ZIKV. New studies are needed to conduct a better mapping and panorama of the congenital Zika syndrome in our state.